A Set of English Instructional Materials Using Task-Based Learning for News Production Management Study Program in STMM MMMTC Yogyakarta - Wicita, Geovanna Gistha (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2015)
The News Production Management Study Program (NPMSP) in STMM MMTC Yogyakarta is a study program that has an English subject in the third semester. Due to the lack of time and materials for the students, English, which they will use a lot in journalism, becomes their barrier in learning. Therefore, this research attempted to develop a set of English instructional materials using task-based learning for the third semester students of the NPMSP STMM MMTC Yogyakarta. This research aimed to answer how the materials are developed and what the materials look like. To gather the information, the researcher adopted Borg Galls (1986) Research and Development (RD) method which was combined with Kemps instructional design model (1977) covering eight flexible steps. Due to time and financial constraints, only five steps of RD were conducted in designing the materials. To gather the information, the researcher conducted some interviews. After designing the materials, the interview was conducted. The interview results showed that the designed materials were good, appropriate, and applicable. Nine suggestions were obtained to revise the materials which covered the level of difficulty of the text, the content of the exercises, the overview of the learning materials, teaching media, lesson plans, instructions, layout, and material implementation. The materials consist of six units. Each unit contains five sessions, namely Whats Up?, Entering the Newsroom, Journalists Project, Entering the News Editor Room, and Lesson Learned.